America's First Network TV Censor: The Work of NBC's Stockton Helffrich / Pondillo, Robert - Pondillo, Robert
merica’ s First Network TV Censor: The Work of NBC’ s Stockton Helffrich is a unique examination of early television censorship, centered around the papers of Stockton Helffrich, the first manager of the censorship department at NBC. Set against the backdrop of postwar America and contextualized by myriad primary sources including original interviews and unpublished material, Helffrich’ s reports illustrate how early censorship of advertising, language, and depictions of sex, violence, and race shaped the new medium.